1984
DOI: 10.1017/s0022215100148091
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of acupuncture in tinnitus

Abstract: The relationship of tinnitus to pain is examined and a theoretical case made out for the possible use of acupuncture in the treatment of tinnitus. A double-blind cross-over controlled trial is described. The use of Visual Analogue Scales (V.A.S.) is discussed in this context. 35 per cent of patients described some benefit from the active treatment only, although we were unable to demonstrate this objectively. Statistical analysis of the group as a whole revealed no significant differences between placebo and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 21 publications
0
55
1
2
Order By: Relevance
“…[234][235][236]241 Two unblinded studies showed a positive result, whereas 4 blinded studies demonstrated no significant effect of acupuncture.…”
Section: Supporting Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[234][235][236]241 Two unblinded studies showed a positive result, whereas 4 blinded studies demonstrated no significant effect of acupuncture.…”
Section: Supporting Textmentioning
confidence: 99%
“…229,230 A systematic review in 2012 on acupuncture for the treatment of tinnitus included 9 RCTs, with a total of 431 participants. 222 Five of the RCTs used manual acupuncture (MA), [231][232][233][234][235] 1 used electroacupuncture (EA), 236 1 used both MA and EA, 237 and the other 2 used scalp acupuncture. 238,239 Five RCTs compared effectiveness of manual or electroacupuncture with sham acupuncture and showed no statistically significant improvement.…”
Section: Supporting Textmentioning
confidence: 99%
“…However, they noted that tinnitus returned to pre-treatment levels at one y ear follow-up 11 . VAS was used by other authors to measure the level of buzzing reported by patients 7,10,11 . VAS is easy and quick to apply, making possible a comparison of results between groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that having multiple sessions of acupuncture administered over a period of time might work better than just a single session. Marks et al 4 believed that some patients responded to acupuncture only if the course of treatment lasted for more than 2 weeks.…”
Section: Acupuncture For Tinnitusmentioning
confidence: 99%
“…Although there are reports that suggest acupuncture is beneficial for tinnitus, acupuncture has not been demonstrated to be efficacious as a treatment for tinnitus with evidence from rigorous randomized controlled trials. 3 Marks et al, 4 however, pointed out that it was challenging to study treatment of a symptom such as tinnitus, which has multiple etiologies; a treatment may work for some etiologies but not for others. There may well be small subgroups of people with tinnitus for whom acupuncture is effective but could not be identified unless very large numbers of study subjects were accrued to distinguish these small groups of responders from the whole population of people with tinnitus.…”
Section: Introduction Wmentioning
confidence: 99%